Investigating the Effective Indicators in Designing Community Rural Schools Using Collaborative Approaches (Case study: Zirkan village of Mashhad) - Faezeh KHosravi; Mahmoud Reza Saghafi; Hamed Kamelnia (مسکن و محیط روستا)
The use of collaborative approach in school design has been considered extensively in the present century. Despite various studies in design using user participation, experience and direct involvement of users in design have been used less in the field of learning environments. Furthermore, in most of the cases, collaborative approach is restricted to the use of primary and lower levels of participation. The participation of low social classes in the field of architecture has been a common feature of collaborative approaches. Therefore, this research aimed at improving the quality of rural schools, and introducing higher levels of participation. It also seek to provide a practical strategy for users’ participation and pay attention to their needs and desires in designing a rural school in a specific region of Iran. Selected area is Zirkan village near to Mashhad (a capital state). The research methodology is a mixed of qualitative and implementing content theoretical analysis. In this regard, firstly, theoretical studies about the participation of users has been expressed. Then, the necessity for participation in the schools’ design, and various models of user participation have been presented. By analyzing the status of the school in this study and the wishes of the residents  using the focus group method, design patterns have been investigated. The results have been obtained through analyzing data collected from the participatory groups (that benefit from participation tools such as visual questionnaire _similar to the "ROLE test"_ expressing their dream, imagination and Dialogue),. Content Analysis of the views of the groups in defining and describing their desired school can introduce the school design pattern in a rural environment. Users’ comments has been discussed on their school’s architecture in several key features including: the form of the building, the characteristics of the interior space (classroom and communication spaces), outdoor spaces ( such as courtyard), materials and some of the spaces needed. Then, in the analysis section, a comparison was made between qualitative and quantitative methods which are correlation analysis and Cronbach's alpha test. According to the results of this comparison, it was found that when the images have been selected in a large number group (ROLE test), the results are more reliable than findings’ correlation. Based on the Cranbach's alpha test and its unacceptable results in this research, it was determined that qualitative results such as (ROLE) has higher validity and quantitative results do not have enough validity for the test. However, reliable results were classified for different school’s spaces from each section of the study group through comparative analysis. Data analysis shows that participants have the highest agreement for the informality of school corridor space and having different playgrounds with the highest score (96%). Moreover, concrete with the lowest score (44%) is their last choice as the building’s materials. Also, providing green space at the building and the use of flowerboxes in outdoor spaces, were another desire of users. Furthermore, participants prefer bright colors, daily light, social space and connection with outdoors as well as facilities for classrooms were among the factors of interests. They considered facilities such as laboratories, libraries, appropriate bathrooms, large prayer hall, and classrooms which are equipped by technology. In addition,  applying informal space were mentioned for the spaces between classes and corridors. Finally colored materials and color variations were the choices of study groups. Using the collaborative approach in relation to school design, especially for the projects which aimed attention to participants’ needs and desires, provides a user-friendly environment and enhance user's desirability and connectivity to the environment. Results indicate that participation has several benefits. Also, participation approach which used in this research has been successful in attracting a wide range of school communities and has been able to explore diverse viewpoints. However, the result will not necessarily be sufficiently precise and variables. Therefore, more extensive and wider range of collaborative and complementary methods is necessary to achieve more accurate results.